Pasado y presente de Floridablanca como objeto de la Historia - Juan Hernández Franco (Mélanges de la Casa de Velázquez)
The main object of this article is to examine how Floridablanca has been analysed by historians. The conclusion we have come to -just as in real time- is that there is more than one Floridablanca. Assessments range from that of an irreproachable minister who guided enlightened despotism to its greatest heights of splendour, to those that focus on his reactionary character and attitudes; however, the happy medium -and hence the fairest appraisal- may well be that of a politician absorbed in reforms, who held back their implementation when he realised that a small but influential sector of political society believed that these reforms would be followed by liberalising outcomes. There is still more of Floridablanca to be analysed, but that must be left to further research. There are good pointers in that direction in the new political history, the circulation of political proposals and their utilisation by absolute monarchies, establishing links to a transnational history; or else his work can be situated in the period that conceptual historians call a Sattelzeit.